Analisis Penggunaan Bahasa Indonesia pada Film “Tenggelamnya Kapal Van Der Wijck” - Billy Andrea Oktiana (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The film "The Sinking of Van Der Wijck's Ship" is the work of the nation's children in which not only tells the visual story but there is the application of Indonesian that can implement the Indonesian people themselves. This analysis is intended to find, research, and assess the use and application of Indonesian in films made by the State of Indonesia. The analytical method used in this study uses qualitative methods where this article focuses on finding errors in the use of language, examining existing vocabulary, and assessing Indonesian pronunciation. This is important so that films are not only a means of entertainment but can provide indirect knowledge about the use of Indonesian.